Apps y medicina: una visión global y la situación chilena - Tala, Álvaro; Vásquez, Eduardo; Rojas, Eric; Marín, Rigoberto (Revista Médica de Chile, 2021)
Mobile applications (Apps) may become effective aids in health care. Health Apps could reduce barriers such as access and costs and could be used to monitor symptoms, behaviors and even treatments. There is more evidence of their usefulness in nutrition, cardiovascular and mental health. Despite this, its current use is predominantly for information purposes. Healthcare App quality evaluation should consider both clinical and technological aspects since the evidence on its clinical effectiveness is still incipient and they have associated risks. In Chile, the use of mobile technology and Apps is increasing, but there are no regulations for their use. There are few national institutions oriented to the creation and development of Apps for healthcare, highlighting the Digital Transformation Committee, part of the Corporation for the Promotion of Production (CORFO) and the National Center for Health Information Systems (CENS). General recommendations for healthcare App development and use have been established. In this process, it would be beneficial to include actors involved in care. Given the progress of healthcare Apps worldwide and nationally, it is important that health professionals develop digital skills to maximize the potential benefit of these technologies.